LC21: A Digital Strategy for the Library of Congress - National Research Council (The National Academies Press, 2000)
Digital information and networks challenge the core practices of libraries, archives, and all organizations with intensive information management needs in many respects—not only in terms of accommodating digital information and technology, but also through the need to develop new economic and organizational models for managing information. LC21: A Digital Strategy for the Library of Congress discusses these challenges and provides recommendations for moving forward at the Library of Congress, the world's largest library. Topics covered in LC21 include digital collections, digital preservation, digital cataloging (metadata), strategic planning, human resources, and general management and budgetary issues. The book identifies and elaborates upon a clear theme for the Library of Congress that is applicable more generally: the digital age calls for much more collaboration and cooperation than in the past. LC21 demonstrates that information-intensive organizations will have to change in fundamental ways to survive and prosper in the digital age.
Keywords: Behavioral and Social Sciences; Education

The Digital Dilemma: Intellectual Property in the Information Age - National Research Council (The National Academies Press, 2000)
Imagine sending a magazine article to 10 friends-making photocopies, putting them in envelopes, adding postage, and mailing them. Now consider how much easier it is to send that article to those 10 friends as an attachment to e-mail. Or to post the article on your own site on the World Wide Web. The ease of modifying or copying digitized material and the proliferation of computer networking have raised fundamental questions about copyright and patent—intellectual property protections rooted in the U.S. Constitution. Hailed for quick and convenient access to a world of material, the Internet also poses serious economic issues for those who create and market that material. If people can so easily send music on the Internet for free, for example, who will pay for music? This book presents the multiple facets of digitized intellectual property, defining terms, identifying key issues, and exploring alternatives. It follows the complex threads of law, business, incentives to creators, the American tradition of access to information, the international context, and the nature of human behavior. Technology is explored for its ability to transfer content and its potential to protect intellectual property rights. The book proposes research and policy recommendations as well as principles for policymaking.
Keywords: Behavioral and Social Sciences; Policy for Science and Technology

Rational Therapeutics for Infants and Children: Workshop Summary - Institute of Medicine (The National Academies Press, 2000)
The Institute of Medicine's (IOM's) Roundtable on Research and Development of Drugs, Biologics, and Medical Devices evolved from the Forum on Drug Development, which was established in 1986. Sponsor representatives and IOM determined the importance of maintaining a neutral setting for discussions regarding long-term and politically sensitive issues justified the need to revise and enhance past efforts. The new Roundtable is intended to be a mechanism by which a broad group of experts from the public* and private sectors can be convened to conduct a dialogue and exchange information related to the development of drugs, biologics, and medical devices. Members have expertise in clinical medicine, pediatrics, clinical pharmacology, health policy, health insurance, industrial management, and product development; and they represent interests that address all facets of public policy issues. From time to time, the Roundtable requests that a workshop be conducted for the purpose of exploring a specific topic in detail and obtaining the views of additional experts. The first workshop for the Roundtable was held on April 14 and 15, 1998, and was entitled Assuring Data Quality and Validity in Clinical Trials for Regulatory Decision Making. The summary on that workshop is available from IOM. This workshop summary covers the second workshop, which was held on May 24 and 25, 1999, and which was aimed at facilitating the development and proper use of drugs, biologics, and medical devices for infants and children. It explores the scientific underpinnings and clinical needs, as well as the regulatory, legal, and ethical issues, raised by this area of research and development.
Keywords: Health and Medicine

Women in the Chemical Workforce: A Workshop Report to the Chemical Sciences Roundtable - National Research Council (The National Academies Press, 2000)
For a period of history no women worked outside the home. Bust as years have gone by and society has changed, Women are working varying jobs every day. They are, however, underrepresented in some sectors of jobs. This includes women in the engineering and science fields. To matters worse, women do not ascend the career ladder as fast as or as far as men do. The impact of this and related problems for science, the academic enterprise, the U.S. economy, and global economic competitiveness have been recently examined. The Chemical Sciences Roundtable evaluate that the demographics of the workforce and the implications for science and society vary, depending on the field of science or engineering. The roundtable has organized a workshop, "Women in the Chemical Workforce," to address issues pertinent to the chemical and chemical engineering workforce as a whole, with an emphasis on the advancement of women. Women in the Chemical Workforce: A Workshop Report to the Chemical Sciences Roundtable includes reports regarding the workshop's three sessions—Context and Overview, Opportunities for Change, and Conditions for Success—as well as presentations by invited speakers, discussions within breakout groups, oral reports from each group.
Keywords: Industry and Labor; Behavioral and Social Sciences; Math, Chemistry, and Physics

Spacecraft Maximum Allowable Concentrations for Selected Airborne Contaminants: Volume 4 - National Research Council (The National Academies Press, 2000)
The National Aeronautics and Space Administration (NASA) is aware of the potential toxicological hazards to crew members that might be associated with prolonged spacecraft missions. Despite major engineering advances in controlling the atmosphere within spacecraft, some contamination of the air appears inevitable. NASA has measured numerous airborne contaminants during space missions. As the missions increase in duration and complexity, ensuring the health and well-being of astronauts traveling and working in this unique environment becomes increasingly difficult. As part of its efforts to promote safe conditions aboard spacecraft, NASA requested the National Research Council (NRC) to develop guidelines for establishing spacecraft maximum allowable concentrations (SMACs) for contaminants, and to review SMACs for various spacecraft contaminants to determine whether NASA's recommended exposure limits are consistent with the guidelines recommended by the subcommittee. In response to this request, the NRC first developed criteria and methods for preparing SMACs for spacecraft contaminants, published in its 1992 report Guidelines for Developing Spacecraft Maximum Allowable Concentrations for Space Station Contaminants. Since then, the NRC's Subcommittee on Spacecraft Maximum Allowable Concentrations has been reviewing NASA's documentation of chemical-specific SMACs. This report is the fourth volume in the series Spacecraft Maximum Allowable Concentrations for Space Station Contaminants. The first volume was published in 1994 and the second and third in 1996. Spacecraft Maximum Allowable Concentrations for Selected Airborne Contaminants: Volume 4 has been reviewed in draft form by individuals chosen for their technical expertise and diverse perspectives in accordance with procedures approved by the NRC's Report Review Committee for reviewing NRC and Institute of Medicine reports. The purpose of that Independent review was to provide candid and critical comments to assist the NRC in making the published report as sound as possible and to ensure that the report meets institutional standards for objectivity, evidence, and responsiveness to the study charge. The review comments and draft manuscript remain confidential to protect the integrity of the deliberative process.
Keywords: Space and Aeronautics; Environment and Environmental Studies

Addressing the Nation's Changing Needs for Biomedical and Behavioral Scientists - National Research Council (The National Academies Press, 2000)
As biomedical and behavioral research progresses into new areas, the number of scientists active in various fields rises and falls, and the health needs of the U.S. population evolve, it is important to ensure that the preparation of future investigators reflects these changes. This book addresses these topics by considering questions such as the following:
Keywords: Health and Medicine

Safe Work in the 21st Century: Education and Training Needs for the Next Decade's Occupational Safety and Health Personnel - Institute of Medicine (The National Academies Press, 2000)
Despite many advances, 20 American workers die each day as a result of occupational injuries. And occupational safety and health (OSH) is becoming even more complex as workers move away from the long-term, fixed-site, employer relationship. This book looks at worker safety in the changing workplace and the challenge of ensuring a supply of top-notch OSH professionals. Recommendations are addressed to federal and state agencies, OSH organizations, educational institutions, employers, unions, and other stakeholders. The committee reviews trends in workforce demographics, the nature of work in the information age, globalization of work, and the revolution in health care delivery—exploring the implications for OSH education and training in the decade ahead. The core professions of OSH (occupational safety, industrial hygiene, and occupational medicine and nursing) and key related roles (employee assistance professional, ergonomist, and occupational health psychologist) are profiled—how many people are in the field, where they work, and what they do. The book reviews in detail the education, training, and education grants available to OSH professionals from public and private sources.
Keywords: Industry and Labor

Bioinformatics: Converting Data to Knowledge - National Research Council (The National Academies Press, 2000)
The goal of this workshop was to bring together bioinformatics stake holders from government, academe, and industry for a day of presentations and dialogue. Fifteen experts identified and discussed some of the most important issues raised by the current flood of biologic data. Topics explored included the importance of database curation, database integration and interoperability, consistency and standards in terminology, error prevention and correction, data provenance, ontology, the importance of maintaining privacy, data mining, and the need for more computer scientists with specialty training in bioinformatics. Although formal conclusions and recommendations will not come from this particular workshop, many insights may be gleaned about the future of this field, from the context of the discussions and presentations described here.
Keywords: Health and Medicine; Biology and Life Sciences

Review of the U.S. Navy Environmental Health Center's Health-Hazard Assessment Process - National Research Council (The National Academies Press, 2000)
A large number of chemicals are used on land at shore facilities, in the air in combat and reconnaissance aircraft, on seas around the world in surface vessels, and in submarine vessels by the navy and marine corps. Although the chemicals used are for the large part harmless, there is a significant amount of chemicals in use that can be health hazards during specific exposure circumstances. The Navy Environmental Health Center (NEHC) is primarily tasked with assessing these hazards. The NEHC completes its tasks by reviewing toxicological and related data and preparing health-hazard assessments (HHAs) for the different chemicals. Since the NEHC is continually asked to develop these HHAs, the National Research Council (NRC) was asked to assess independently the validity and effectiveness of NEHC's HHA process, in order to determine whether the process as implemented provides the Navy with the best, comprehensive, and defensible evaluations of health hazards and to identify any elements that might require improvement. The task was assigned to the Board on Environmental Studies and Toxicology's Committee on Toxicology's (COT's) Subcommittee on Toxicological hazard and Risk Assessment. Review of the U.S. Navy Environmental Health Center's Health-Hazard Assessment Process presents the subcommittee's report. The report is the work of expertise in general toxicology, inhalation toxicology, epidemiology, neurotoxicology, immunotoxicology, reproductive and developmental toxicology, pharmacology, medicine, risk assessment, and biostatistics. It is based on its review of documents provided by NEHC, presentations by NEHC personnel, and site visits to NEHC in Norfolk, Virginia and an aircraft carrier in San Diego, California.
Keywords: Environment and Environmental Studies; Conflict and Security Issues

Veterans and Agent Orange: Herbicide/Dioxin Exposure and Type 2 Diabetes - Institute of Medicine (The National Academies Press, 2000)
In response to the concerns voiced by Vietnam veterans and their families, Congress called upon the National Academy of Sciences (NAS) to review the scientific evidence on the possible health effects of exposure to Agent Orange and other herbicides. This call resulted in the creation of the first NAS Institute of Medicine Committee to Review the Health Effects in Vietnam Veterans of Exposure to Herbicides in 1992. The committee published its initial findings in the 1994 report Veterans and Agent Orange: Health Effects of Herbicides Used in Vietnam. This report is the result of a 1999 request from the Department of Veterans Affairs (DVA) under the aegis of the Veterans and Agent Orange research program. Specifically, DVA asked the committee to examine evidence regarding the association, if any, between Type 2 diabetes and exposure to dioxin and other chemical compounds in herbicides used in Vietnam. Veterans and Agent Orange: Herbicide/Dioxin Exposure and Type 2 Diabetes reviews the scientific evidence regarding the association, if any, between Type 2 diabetes1 and exposure to dioxin2 and other chemical compounds in herbicides used in Vietnam. This report examines, to the extent that available data permitted meaningful determinations, (1) whether a statistical association with herbicide exposure exists, taking into account the strength of the scientific evidence and the appropriateness of the statistical and epidemiologic methods used to detect the association; (2) the increased risk of the disease among those exposed to herbicides during Vietnam service; and (3) whether there is a plausible biological mechanism or other evidence of a causal relationship between herbicide exposure and the disease.
Keywords: Health and Medicine

Graduate Education in the Chemical Sciences: Issues for the 21st Century: Report of a Workshop - National Research Council (The National Academies Press, 2000)
Graduate Education in the Chemical Sciences is a summary of the December 1999 workshop, "Graduate Education in the Chemical Sciences: Issues for the 21st Century." This workshop discussed the various features of graduate education in chemical science and technology. Using case histories and their individual experiences, speakers examined the current status of graduate education in the chemical sciences, identified problems and opportunities, and discussed possible strategies for improving the system. The discussion was oriented toward the goal of generating graduates who are well prepared to advance the chemical sciences in academia, government, and industry in the next 5 to 10 years.
Keywords: Education

Summary of a Workshop on Information Technology Research for Federal Statistics - National Research Council (The National Academies Press, 2000)
Part of an in-depth study of how information technology research and development could more effectively support advances in the use of information technology (IT) in government, Summary of a Workshop on Information Technology Research for Federal Statistics explores IT research opportunities of relevance to the collection, analysis, and dissemination of federal statistics. On February 9 and 10, 1999, participants from a number of communities—IT research, IT research management, federal statistics, and academic statistics—met to identify ways to foster interaction among computing and communications researchers, federal managers, and professionals in specific domains that could lead to collaborative research efforts. By establishing research links between these communities and creating collaborative mechanisms aimed at meeting relevant requirements, this workshop promoted thinking in the computing and communications research community and throughout government about possibilities for advances in technology that will support a variety of digital initiatives by the government.
Keywords: Computers and Information Technology; Behavioral and Social Sciences; Surveys and Statistics

Methods for Developing Spacecraft Water Exposure Guidelines - National Research Council (The National Academies Press, 2000)
The National Aeronautics and Space Administration (NASA) maintains an active interest in the environmental conditions associated with living and working in spacecraft and identifying hazards that might adversely affect the health and well-being of crew members. Despite major engineering advances in controlling the spacecraft environment, some water and air contamination appears to be inevitable. Several hundred chemical species are likely to be found in the closed environment of the spacecraft, and as the frequency, complexity, and duration of human space flight increase, identifying and understanding significant health hazards will become more complicated and more critical for the success of the missions. NASA asked the National Research Council (NRC) Committee on Toxicology to develop guidelines, similar to those developed by the NRC in 1992 for airborne substances, for examining the likelihood of adverse effects from water contaminants on the health and performance of spacecraft crews. In this report, the Subcommittee on Spacecraft Water Exposure Guidelines (SWEGs) examines what is known about water contaminants in spacecraft, the adequacy of current risk assessment methods, and the toxicologic issues of greatest concern.
Keywords: Space and Aeronautics

Networking Health: Prescriptions for the Internet - National Research Council (The National Academies Press, 2000)
Consumer health websites have garnered considerable media attention, but only begin to scratch the surface of the more pervasive transformations the Internet could bring to health and health care. Networking Health examines ways in which the Internet may become a routine part of health care delivery and payment, public health, health education, and biomedical research. Building upon a series of site visits, this book:
Keywords: Computers and Information Technology; Health and Medicine

Inquiry and the National Science Education Standards: A Guide for Teaching and Learning - National Research Council (The National Academies Press, 2000)
Humans, especially children, are naturally curious. Yet, people often balk at the thought of learning science—the "eyes glazed over" syndrome. Teachers may find teaching science a major challenge in an era when science ranges from the hardly imaginable quark to the distant, blazing quasar. Inquiry and the National Science Education Standards is the book that educators have been waiting for—a practical guide to teaching inquiry and teaching through inquiry, as recommended by the National Science Education Standards. This will be an important resource for educators who must help school boards, parents, and teachers understand "why we can't teach the way we used to."
Keywords: Education

Toxicological Risks of Selected Flame-Retardant Chemicals - National Research Council (The National Academies Press, 2000)
Ignition of upholstered furniture by small open flames from matches, cigarette lighters, and candles is one of the leading causes of residential-fire deaths in the United States. These fires accounted for about 16% of civilian fire deaths in 1996. On average, each year since 1990, about 90 deaths (primarily of children), 440 injuries, and property losses amounting to 50 million dollars have resulted from fires caused by the ignition of upholstered furniture by small open flames. Certain commercial seating products (such as aircraft and bus seats) are subject to flammability standards and sometimes incorporate FR-treated upholstery cover materials, but there is no federal-government requirement for residential upholstered furniture, and it is generally not treated with FR chemicals. It is estimated that less than 0.2% of all U.S. residential upholstery fabric is treated with flame-retardant (FR) chemicals. The Consumer Product Safety Act of 1972 created the U.S. Consumer Product Safety Commission (CPSC) as an independent federal regulatory agency whose mission is to protect the public from unreasonable risks of injury and death associated with consumer products. CPSC also administers the Flammable Fabrics Act, under which it regulates flammability hazards and the Federal Hazardous Substances Act (FHSA), which regulates hazardous substances including chemicals. In 1993, the National Association of State Fire Marshals petitioned CPSC to issue a performance-based flammability standard for upholstered furniture to reduce the risk of residential fires. The Commission granted that portion of the petition relating to small open flame ignition risks. In response to concerns regarding the safety of FR chemicals, Congress, in the fiscal year 1999 appropriations report for CPSC, requested that the National Research Council conduct an independent study of the health risks to consumers posed by exposure to FR chemicals that are likely to be used in residential upholstered furniture to meet a CPSC standard. The National Research Council assigned the project to the Committee on Toxicology (COT) of the Commission on Life Sciences' Board on Environmental Studies and Toxicology. COT convened the Subcommittee on Flame-Retardant Chemicals, which prepared this report. Subcommittee members were chosen for their recognized expertise in toxicology, pharmacology, epidemiology, chemistry, exposure assessment, risk assessment, and biostatistics. Toxicological Risks of Selected Flame-Retardant Chemicals is organized into 18 chapters and two appendices. Chapter 2 describes the risk assessment process used by the subcommittee in determining the risk associated with potential exposure to the various FR chemicals. Chapter 3 describes the method the subcommittee used to measure and estimate the intensity, frequency, extent, and duration of human exposure to FR chemicals. Chapters 4-19 provide the subcommittee's review and assessment of health risks posed by exposure to each of the 16 FR chemicals. Data gaps and research needs are provided at the end of these chapters.
Keywords: Environment and Environmental Studies; Space and Aeronautics

Environmental Issues in Pacific Northwest Forest Management - National Research Council (The National Academies Press, 2000)
People are demanding more of the goods, services, and amenities provided by the forests of the Pacific Northwest, but the finiteness of the supply has become clear. This issue involves complex questions of biology, economics, social values, community life, and federal intervention. Forests of the Pacific Northwest explains that economic and aesthetic benefits can be sustained through new approaches to management, proposes general goals for forest management, and discusses strategies for achieving them. Recommendations address restoration of damaged areas, management for multiple uses, dispute resolution, and federal authority. The volume explores the market role of Pacific Northwest wood products and looks at the implications if other regions should be expected to make up for reduced timber harvests. The book also reviews the health of the forested ecosystems of the region, evaluating the effects of past forest use patterns and management practices. It discusses the biological importance, social significance, and management of old-growth as well as late-succession forests. This volume will be of interest to public officials, policymakers, the forest products industry, environmental advocates, researchers, and concerned residents.
Keywords: Earth Sciences; Environment and Environmental Studies

Buzzwords: A Scientist Muses on Sex, Bugs, and Rock 'n' Roll - Berenbaum, May R. (The National Academies Press, 2000)
What sort of person devotes their life to the study of bugs? How do you picture your average, every-day entomologist? "I've been photographed on several occasions," writes author May Berenbaum, "and it seems that every time, photographers ask me to pose in one of three ways: seated in front of a microscope, with an insect (usually a cockroach) on my face, or with an insect net clutched in my hand." In Buzzwords, Berenbaum expertly blows away these stereotypes with short takes on all things entomological—from the story of a pet ant kept for 14 years to major motion pictures featuring cockroaches. Buzzwords showcases the Best of Berenbaum, a selection from her humor column in the American Entomologist professional journal, accompanied by a number of original pieces written for this book. "I know people are reading these columns," she notes, "because they write me letters that point out all the mistakes I've made!" The book comes in four parts:
Keywords: Explore Science; Agriculture

Clearing the Air: Asthma and Indoor Air Exposures - Institute of Medicine (The National Academies Press, 2000)
Since about 1980, asthma prevalence and asthma-related hospitalizations and deaths have increased substantially, especially among children. Of particular concern is the high mortality rate among African Americans with asthma. Recent studies have suggested that indoor exposures—to dust mites, cockroaches, mold, pet dander, tobacco smoke, and other biological and chemical pollutants—may influence the disease course of asthma. To ensure an appropriate response, public health and education officials have sought a science-based assessment of asthma and its relationship to indoor air exposures. Clearing the Air meets this need. This book examines how indoor pollutants contribute to asthma—its causation, prevalence, triggering, and severity. The committee discusses asthma among the general population and in sensitive subpopulations including children, low-income individuals, and urban residents. Based on the most current findings, the book also evaluates the scientific basis for mitigating the effects of indoor air pollutants implicated in asthma. The committee identifies priorities for public health policy, public education outreach, preventive intervention, and further research.
Keywords: Environment and Environmental Studies; Health and Medicine

Incorporating Science, Economics, and Sociology in Developing Sanitary and Phytosanitary Standards in International Trade: Proceedings of a Conference - National Research Council (The National Academies Press, 2000)
The rapid expansion of international trade has brought to the fore issues of conflicting national regulations in the area of plant, animal, and human health. These problems include the concern that regulations designed to protect health can also be used for protection of domestic producers against international competition. At a time when progressive tariff reform has opened up markets and facilitated trade, in part responding to consumer demands for access to a wide choice of products and services at reasonable prices, closer scrutiny of regulatory measures has become increasingly important. At the same time, there are clear differences among countries and cultures as to the types of risk citizens are willing to accept. The activities of this conference were based on the premise that risk analyses (i.e., risk assessment, management, and communication) are not exclusively the domain of the biological and natural sciences; the social sciences play a prominent role in describing how people in different contexts perceive and respond to risks. Any effort to manage sanitary and phytosanitary (SPS) issues in international trade must integrate all the sciences to develop practices for risk assessment, management, and communication that recognize international diversity in culture, experience, and institutions. Uniform international standards can help, but no such norms are likely to be acceptable to all countries. Political and administrative structures also differ, causing differences in approaches and outcomes even when basic aims are compatible. Clearly there is considerable room for confusion and mistrust. The issue is how to balance the individual regulatory needs and approaches of countries with the goal of promoting freer trade. This issue arises not only for SPS standards but also in regard to regulations that affect other areas such as environmental quality, working conditions, and the exercise of intellectual property rights. This conference focused on these issues in the specific area of SPS measures. This area includes provisions to protect plant and animal health and life and, more generally, the environment, and regulations that protect humans from foodborne risks. The Society for Risk Analysis defines a risk as the potential for realization of unwanted, adverse consequences to human life, health, property, or the environment; estimation of risk is usually based on the expected value of the conditional probability of the event occurring times the consequence of the event given that it has occurred. The task of this conference and of this report was to elucidate the place of science, culture, politics, and economics in the design and implementation of SPS measures and in their international management. The goal was to explore the critical roles and the limitations of the biological and natural sciences and the social sciences, such as economics, sociology, anthropology, philosophy, and political science in the management of SPS issues and in judging whether particular SPS measures create unacceptable barriers to international trade. The conference's objective also was to consider the elements that would compose a multidisciplinary analytical framework for SPS decision making and needs for future research.
Keywords: Food and Nutrition; Health and Medicine